3rd Global Conference on Business and Social Science-201 5, GCBSS-2615, 15- 17 December 20 1 5, Kuala Lmpur, Malaysia Organizational Justice: A Conceptual Discussion - Tan, Fee Yean; Yusof, Ab. Aziz (Elsevier, 2015)
Organizational justice consists of three dimensions, namely* disb%utive, pro&&d and interactional justice. Organizational justice affects not only organizational performance, but to a large extent, also determines the economic wellbeing of an employee. Thus, organizational justice has a great impact on organizations, especially with regards to harmonizing the relationship between employer and employees. Treating employees unfa~rlyc can create negative attitude (t.g., refusal to follow instructions, sub-standard work performance, intentionally violating company des and regulations, etc.) among employees towards management Hence, several studies have been undertaken by past researchers to understand the issue of fairness in the workplace. Based on past studies, this paper aims to discuss the conceptualization of organizational justice.